The Influence of Confucian Values: Students’ Understandings of Classroom Behaviours and Learning Practices in a University in Central China - Song, Jinhua (Auckland University of Technology, 2014)
The research aims to investigate the influences of Confucian values on university students’ classroom behaviours and learning practices in Central China. Using a Foucauldian 'genealogical approach' the thesis investigated the extent to which contemporary students in a Western/central university still employ Confucius's ideas in their thinking about education, and in their own learning practices, in the classroom and outside it. The interviews showed how deeply embedded Confucian ideas were: to the extent that they were part of the students' conception of their own identities, despite the inroads of competing ideologies. The results highlighted individual students’ ability to reflect on Confucian values, and demonstrated the significant role played by students’ notice of their own identities in dealing with the influence of Confucian values. The study identified some similarities to and differences from existing literature. It made a new contribution to knowledge by exploring the overlooked element of Confucius' emphasis on joy in learning. It broke new grounds by exploring the tensions in student’s minds as they reconciled Confucian traditions, Maoist ideas and western ideas. The students’ views gave fresh insights into students’ agential powers and structural or cultural influences in the area of learning. This research provided an opportunity for students to reflect on their individual practices in their environment, to voice their concerns, and to uncover their own deep assumptions and tradition by unearthing the influence of Confucian values on their learning ideas, behaviours and practices. All teachers of Chinese students can benefit by being aware of these influences on their students. The research results could be used to develop university policies. Also learning skills support and teaching pace might be made culturally relevant, especially when students come from a Chinese cultural background.
Keywords: Confucian influences; Classroom behaviours; Learning practices; Students' understandings; Foucauldian genelogical approach; Central China